Impact of beaver dam analogues on hydrology in a semi‐arid floodplain. Issue 7 (13th July 2021) - Pearce, Casey; Vidon, Philippe; Lautz, Laura; Kelleher, Christa; Davis, Julianne
Abstract: Natural beaver ponds help connect the stream to the floodplain, maintain late summer low flows and reduce peak flow during high flow events by offering temporary surface water (SW) storage. When beavers are extirpated from the landscape, stream degradation often ensues. This study assesses the impact of beaver dam analogues (BDA) as a stream restoration technique to help maintain low flow water levels and enhance stream‐floodplain interactions on a seasonal basis in Red Canyon Creek, Lander, WY. BDAs increased SW and groundwater (GW) levels, favoured the occurrence of flow reversals (i.e., stream‐to‐floodplain GW flow) during high flow events associated with mid‐winter and early‐spring thaw events, and reduced the groundwater‐to‐stream hydraulic gradient on an annual basis. Although GW temperatures varied seasonally, relatively cooler GW temperatures were observed in the BDA impacted reach compared to the control reach away from BDA influence. BDAs however did not significantly impact stream temperatures. Overall, results suggest that when installed in sequence, BDA complexes can successfully reconnect the stream to its floodplain, and ultimately increase SW‐GW exchange at the floodplain scale by allowing flow reversals to occur and by reducing the GW to stream hydraulic gradient. Although BDAs built with fence posts, willow branches, sediments and small boulders are naturally porous and require regular maintenance, this study also highlights the viability of small BDAs as a restoration practice to enhance landscape resilience to drought and high flow events in deeply incised channels where beavers would not come back naturally. Abstract : Beaver dam analogues (BDA) increased surface water (SW) and groundwater (GW) levels, favoured the occurrence of flow reversals (i.e., stream‐to‐floodplain GW flow) during high flow events associated with mid‐winter and early‐spring thaw events, and reduced the groundwater‐to‐stream hydraulic gradient on an annual basis. Although GW temperatures varied seasonally, relatively cooler GW temperatures were observed in the BDA impacted reach compared to the control reach away from BDA influence. BDAs however did not significantly impact stream temperatures.